Design and Development of Dielectric Resonator Antenna Using Ceramic Materials: An Overview - Pandey S.; Kumar D.; Parkash O.; Pandey L. (My University, 2025)
The basics of design of microstrip aperture-coupled ceramic rectangular dielectric resonator antenna (RDRA) are given. Methods of estimation of antenna dimensions, impedance matching, excitation procedure and choice of suitable materials to be used in the fabrication are briefly described. The RDRA dimensions are obtained by solving the transcendental equation derived from Maxwell equations using dielectric waveguide model. Some ceramics are found useful for fabrication of DRAs that yield large bandwidth and gain are summarized. An attempt to explore the application of dielectric materials having small dielectric loss (tan δ > 0.01) has been made by developing RDRA configurations using one, two and three element arrays, and effect of dielectric loss on their performance is studied using ANSYS HFSS simulations. For a RDRA array comprising of three elements, where the middle parasitic element has small dielectric loss (tan δ ~ 0.1) and the outer elements are aperture coupled, the gain decreases only by 2.7%, while the bandwidth is enhanced by 3%. The findings indicate the possibility of using ceramics having small dielectric loss such as Ba1−xSrxTiO3 (x = 0.35, tan δ ~ 0.1) with some trade-off with gain by using suitable designs. Equivalent circuit modelling useful in understanding the performance of microstrip aperture-coupled RDRA is also presented. © 2019, The Indian Institute of Metals - IIM.